Pengaruh Penambahan Serat Polypropylene Terhadap Sifat Mekanis Beton Normal - Yuri Khairizal; Alex Kurniawandy; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research studies the mechanical properties of polypropylene concrete consist of compressive strength, modulus of elasticity, splitting tensile strength, flexural strength and deflection. Polypropylene fiber is a kind of plastic fiber that specially produced with high technology. Application of this polypropylene fiber aim to improve the mechanical propertiesof normal concrete. The specimens are cylinder and beam shapes. The variety that use is additional of polypropylene fiber at 0,0 kg/m3, 0,2 kg/m3, 0,4 kg/m3, 0,6 kg/m3, 0,8 kg/m3 and 1,0 kg/m3. The result of research shows that highest compressive strength and modulus of elasticity of concrete occurred at 0,4 kg/m3 polypropylene various. Highest splitting tensile strength and flexural strength of concrete occurs at 1,0 kg/m3 polypropylene fiber various. In generally, deflection test shows improvement within addition of polypropylene fiber. According to the result of research, additional polypropylene fiber into concrete mixture can improve the mechanical properties of concrete, especially compressive strength, modulus of elasticity, splitting tensile strength and deflection of concrete.Keyword : polypropylene fiber, mechanical properties, compressive strength, splitting tensile strength, flexural strength